Analyzing the Influence of Non-Performing Assets: A Comparative Study between SBI and HDFC - Balyan, Sneha; Singh, Netra Pal (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
Non-performing assets (NPAs) pose an enduring and intricate challenge within the banking sector, carrying far-reaching consequences for both financial stability and broader economic growth. This paper provides an in-depth analysis of NPAs and their impact on the financial performance of HDFC and SBI. Based on the analysis of the NPA data of the two banks, it is found that the NPA ratio for State Bank of India is in the range of 1.02%-5.73%, which is on the higher side in comparison to the NPA of HDFC, which lies between 0.20%-0.64% for the period 2007-8 to 2021-2022. In both cases, NPA has a negative impact on profitability, but it is much higher in SBI. These findings may help SBI reinvent its credit policy and the credited process of its credit business to different customer segments.